Kingdom of Lesotho : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2022)
In response to a request from the authorities and as part of the Data for Decisions (D4D)1 funded project under the submodule for Fiscal and Debt reporting, a government finance statistics (GFS) technical assistance (TA) mission was held remotely with the Lesotho Ministry of Finance (MOF) during April 5-16, 2021. Previous TA missions under the Enhanced Data Dissemination Initiative (EDDI2) over the period spanning from 2016 to 2020 assisted the MOF to improve GFS compilation and dissemination for the budgetary central government (BCG) and inspired action to broaden data coverage to include local governments and extrabudgetary units (EBUs) with the aim to compile and disseminate consolidated general government GFS. Preliminary local government GFS have now been compiled, and data collected for selected state-owned enterprises (SOEs) and parastatals, including non-market SOEs that can now contribute to preliminary general government GFS to be compiled.